Enzymatic modification of Fish Gelatin and Beet Pectin using Horseradish peroxidase - Ebenezer Asiamah; Dominic Aboagye; Ahmed A. Zaky; Charles Asakiya; Ethel Juliet Serwa Blessie (Food Hydrocolloids for Health, 2022)
The Fish Gelatin (FG), a good alternative for unhealthy and limited socio-cultural mammalian gelatin appears to possess endogenous structural limitations. The goal of this work was to use enzymatic crosslinking to modify cold-water Fish Gelatin (FG) with Beet Pectin. Reaction conditions were optimized by a single factorial experiment and covalent crosslinking was measured by ultraviolet (UV)-Vis spectroscopy at 340 nm to indicate Horseradish Peroxidase (HRP) catalyzes Beet Pectin (BP). At 50 °C for 4 h, the highest weight ratio of heterologous adducts between FG-BP was 1:3, with HRP and Hydrogen peroxide (H2O2) of 2 µg/mL and 0.067%, (v/v), respectively. Intermolecular cross-linking was found between treated samples using ATR-FTIR and Sodium Dodecyl Sulphur and Polyacrylamide Gel Electrophoresis (SDS-PAGE). The heterologous product, control FG, and BP as well as a mixture of untreated FG-BP had a β-sheet of 41.14%, 39.65%, 39.9%, and 40.0%, respectively. The maximum reduction in elution was obtained in heterogeneous FG-BP complex. Furthermore, a schematic mechanism for Cold-water Fish Gelatin and Beet Pectin was proposed. Overall, peroxidase crosslinked BP was able to modify cold-water Fish Gelatin. The use of Horseradish peroxidase on Fish Gelatin could provide a practical way of building the FG-BP complex as a basis for understanding the FG functionalities comprehensively.